2009
DOI: 10.2976/1.3067922
|View full text |Cite
|
Sign up to set email alerts
|

Why does GM1 induce a potent beneficial response to experimental Chagas disease?

Abstract: Being one of the world's neglected diseases, Chagas has neither a vaccine nor a satisfactory therapy. Inoculation of murine models with the ganglioside GM1 has shown a strikingly nonlinear effect, leading to a strong decrease in parasite load at low doses but reverting to a load increase at high doses. Cardiocyte destruction concomitant with the disease is also significantly reduced by a moderate application of GM1. A mathematical model for the interaction between the parasite and the immune system is shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Although GM1 treatment conserved native rates of triacyclglycerols and cholesterol of cardiomyocytes plasma membranes, Trypanosoma cruzi infection and GM1 treatment diminished membrane microviscosity of cardiac myocytes plasma membranes, but GM1 effect was more pronounced., see Table VI. (results from [28])…”
Section: Fluorescence Anisotropy Measurementmentioning
confidence: 98%
“…Although GM1 treatment conserved native rates of triacyclglycerols and cholesterol of cardiomyocytes plasma membranes, Trypanosoma cruzi infection and GM1 treatment diminished membrane microviscosity of cardiac myocytes plasma membranes, but GM1 effect was more pronounced., see Table VI. (results from [28])…”
Section: Fluorescence Anisotropy Measurementmentioning
confidence: 98%
“…(2) La replicación binaria intracelular del T. cruzi en su estado amastigotico es considerada a través del número de células infectadas r(t) [20,21,22,23]. Para introducir el efecto de la reacción inmune celular, y siguiendo el modelo propuesto por Yang [24], consideraremos dos poblaciones: las células T citotóxicas no-activas, Q i (t), y las células T citotóxicas activas c i (t).…”
Section: El Modelounclassified
“…5 More recently, fluorescence experiments showed that the addition of GM1 results in an increase in microfluidity in both infected and noninfected cardiocytes. 9 This increase in fluidity is assumed to lead to a decrease in the citotoxicity η = η(c), where c is the GM1 concentration. Since the amastigote replication time Ω should not be affected by the ganglioside, the number of parasites liberated in a cell breakup, N r , increases according to the relation N r = 2 1 ηΩ .…”
Section: Gm1 Beneficial Actionmentioning
confidence: 99%
“…Since the amastigote replication time Ω should not be affected by the ganglioside, the number of parasites liberated in a cell breakup, N r , increases according to the relation N r = 2 1 ηΩ . If parasite penetration is impaired by GM1 action, 9 the infectivity ζ = ζ(c) is also reduced. The simplest way to account for the GM1 effect on infectivity and cytotoxicity is to assume the following functional dependences on c,…”
Section: Gm1 Beneficial Actionmentioning
confidence: 99%